Place-based learning: A framework for building a multilevel approach from companies (Revista Lusófona de Educação, 2022)
Company visits are common in Master of Business Administration (MBA) programmes, but much less frequent in undergraduate business education. The purpose of this article is to advocate a framework for place-based learning multilevel approach, illustrating how each level can be incorporated into a sociology of organizations course in the bachelor of business administration featuring company visits. Considering empirical works and research lines developed over recent years, this framework highlights the understanding of organizational, group and individual levels through reflexive, active and collaborative practices. These practices are carried out by students and teachers, in close articulation with the members of the business communities, inside and outside of the classroom, bringing with it a sense of learning teaching unity that promotes interdependent and challenging learning ecologies. To conclude, it is argued that place-based learning needs to explore a deeper reflection on the interconnections and complexities between the organizational, group and individual levels. More effective teaching and learning strategies must be promote with a greater connection to a business organizational environment becoming more uncertain and volatile.Keywords: Place-based learning; multilevel approach; business education; companies.